2016
DOI: 10.1088/1748-6041/11/4/045008
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial ability and osteogenic activity of porous Sr/Ag-containing TiO 2 coatings

Abstract: Implant-associated infection and poor osseointegration remains a major clinical challenge in Ti-based implant materials. A versatile strategy to endow Ti-based implants with long-term antibacterial ability as well as better osteogenic activity is highly desirable for high quality implantation. Strontium (Sr) has been shown to be a significant element to favor bone growth by promoting new bone formation and inhibiting bone resorption. In this study, a novel duplex-treatment technique encompassing magnetron sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(112 citation statements)
references
References 51 publications
10
101
1
Order By: Relevance
“…Bonnelye et al have reported that 0.1 m M of Sr 2+ promotes the differentiation osteoblast precursors into mature osteoblasts, increases bone nodule number, and enhances the expression of osteoblastic markers ALP, bonesialoprotein and osteocalcin . However, high doses of strontium may induce defective bone mineralization and reduce the 25‐hydroxyvitamin D3‐hydroxylase activity …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bonnelye et al have reported that 0.1 m M of Sr 2+ promotes the differentiation osteoblast precursors into mature osteoblasts, increases bone nodule number, and enhances the expression of osteoblastic markers ALP, bonesialoprotein and osteocalcin . However, high doses of strontium may induce defective bone mineralization and reduce the 25‐hydroxyvitamin D3‐hydroxylase activity …”
Section: Resultsmentioning
confidence: 99%
“…For bone scaffold materials, osteogenic property is an important property to induce in vivo bone formation in the absence of osteogenic factors . Some trace elements may affect bone formation and resorption through direct or indirect effects on bone cells or bone mineral . Because LDHs possess compositional flexibility, it is feasible to improve the biocompatibility and osteogenic differentiation of LDHs by the substitution of the divalent cation ( M 2+ ) and trivalent cation ( M 3+ ) with essential bioactive elements such as Mg, Fe, Sr, and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strontium (Sr) which is known to improve osseointegration, has also been incorporated through PEO on the sputtering‐deposited TiAg layer by adding strontium acetate hemihydrate in the electrolyte. The resultant layer with antibacterial behavior also exhibited excellent adhesion, proliferation and differentiation of preosteoblastic cells due to the combined effect of porosity and the presence of Sr …”
Section: Antibacterial Coatings Through Peomentioning
confidence: 99%
“…On this basis, He et al [112] fabricated porous Ag/Sr-containing TiO2 coatings via the similar method in the MAO electrolyte containing 0.167 M CA, 0.02 M β-GP and 0.033 M strontium acetate hemihydrate (SA). The coating displayed long-lasting antibacterial ability even up to 28 d due to the incorporation of Ag.…”
Section: Mao Assisted By Msmentioning
confidence: 99%